Mechanism modeling of optimal excess air coefficient for operating in coal fired boiler. (15th December 2022) - Wang, Yanhong; Li, Xiaoyu; Mao, Tianqin; Hu, Pengfei; Li, Xingcan; GuanWang,
Abstract: Optimization of excess air coefficient is extremely significant for boiler operating performance. Currently theoretical modeling of optimal excess air coefficient is still an intractable technical issue for pulverized coal boiler, limits further efficient utilization of coal. In this work, a mechanistic optimization model considering influence mechanisms was developed to model optimal excess air coefficient under partial boiler loads. To investigate efficiency of analyzed steam boiler, indirect method and individual boiler losses computation was applied. The accuracy of model results was verified at three different partial loads. Subsequently, modeling approach is used for a case study on 660 MW boiler. Influence mechanism between excess air coefficient and boiler operating parameters was graphically analyzed and meticulously discussed. Optimum energy efficiency and exergy efficiency of boiler were determined and given accurately. The developed model allows performing calculations for variable input conditions to determine total boiler efficiency and basic technical parameters. In addition, presented methods were applied to identify changing of boiler efficiency and basic boiler parameters during operation with different loads and burning different coal types. The results were presented in the form of coal consumption rate, total boiler efficiency and boiler losses as function of excess air coefficient, load and coal type. This work formulaically reveals evolution mechanism of boiler parameters and accurately determines the optimal excess air coefficient. It can be used as a means of boiler combustion optimization and adjustment. Highlights: Nonlinear analysis model of boiler involving variation of excess air coefficient are constructed. Optimum excess air coefficient and best boiler thermal efficiency can be determined. Heat loss of incomplete solid combustion and exhaust gas temperature are carefully considered. Influence mechanism of excess air coefficient on boiler performance is revealed.